Rapid gut dysbiosis induced by stroke exacerbates brain infarction in turn. Issue 8 (8th February 2021) - Xu, Kaiyu; Gao, Xuxuan; Xia, Genghong; Chen, Muxuan; Zeng, Nianyi; Wang, Shan; You, Chao; Tian, Xiaolin; Di, Huiling; Tang, Wenli; Li, Pan; Wang, Huidi; et al.
Abstract : Objective: Stroke is a leading cause of death and disability worldwide. Neuroprotective approaches have failed in clinical trials, thus warranting therapeutic innovations with alternative targets. The gut microbiota is an important contributor to many risk factors for stroke. However, the bidirectional interactions between stroke and gut microbiota remain largely unknown. Design: We performed two clinical cohort studies to capture the gut dysbiosis dynamics after stroke and their relationship with stroke prognosis. Then, we used a middle cerebral artery occlusion model to explore gut dysbiosis post-stroke in mice and address the causative relationship between acute ischaemic stroke and gut dysbiosis. Finally, we tested whether aminoguanidine, superoxide dismutase and tungstate can alleviate post-stroke brain infarction by restoring gut dysbiosis. Results: Brain ischaemia rapidly induced intestinal ischaemia and produced excessive nitrate through free radical reactions, resulting in gut dysbiosis with Enterobacteriaceae expansion. Enterobacteriaceae enrichment exacerbated brain infarction by enhancing systemic inflammation and is an independent risk factor for the primary poor outcome of patients with stroke. Administering aminoguanidine or superoxide dismutase to diminish nitrate generation or administering tungstate to inhibit nitrate respiration all resulted in suppressed Enterobacteriaceae overgrowth, reduced systemic inflammation and alleviated brain infarction. These effects were gut microbiome dependent and indicated the translational value of the brain–gut axis in stroke treatment. Conclusions: This study reveals a reciprocal relationship between stroke and gut dysbiosis. Ischaemic stroke rapidly triggers gut microbiome dysbiosis with Enterobacteriaceae overgrowth that in turn exacerbates brain infarction.